TRANSFORMATION OF THE EDUCATION SYSTEM: REASONS, TENDENCIES, PERSPECTIVES - Irina V. Veshneva; Rustam A. Singatulin (Высшее образование в России, 2016)
The transformation of the sociocultural relations is accompanied by severe 147 crises and revolutions. These transformations are reflected in education systems. To develop the right strategy of Russian education it is important to identify the causes, the trends, and the perspectives of this education transformation. The visible trends corroborate that the current stage is a transition. The authors compare classical, distance and virtual learning systems and show the role, objectives and results of the participants of learning process. An active introduction of information technologies in learning process consumes the substantial resources of the whole society, but we shouldn’t underestimate the importance of virtual training systems development, otherwise Russia can loss the strategic advantages in the development of the entire education system. Application of virtual reality technology enables to enhance the training effectiveness by dozens of times. The article substantiates the necessity of forming a strategy of priority development of the virtual learning rather than distance learning and reveals the social, educational, scientific and technical problems of the group of virtual training systems.